THE DIFFERENCES OF ANTITHROMBIN III, FIBRINOGEN, AND TROPONIN I LEVELS BETWEEN ACUTE ISCHEMIC STROKE AND ACUTE HEMORRHAGIC STROKE - Listra Isabela Barus, Puji Pinta O. Sinurat & Chairil Amin Batubara (International Journal of Research Science and Management, 2019)
Introduction: Plasma antithrombin III associated with fibrinogen might help the risk assessment of acute ischemic stroke, but studies that discuss those levels in hemorrhagic stroke are still limited. Troponin I is a cardiac enzyme that has high sensitivity and specificity in the detection of heart injury after stroke. The purpose of this study is to determine the differences of antithrombin III, fibrinogen, and troponin I levels between acute ischemic stroke and acute hemorrhagic stroke. Method: This study used a descriptive analytic study with a cross sectional design. A total of 52 research subjects, consisting of 26 acute ischemic stroke patients and 26 acute hemorrhagic stroke patients were taken by consecutive non-random sampling method. The blood samples from the subjects that have been diagnosed by history taking, physical examination and head CT scan, were taken for examination of antithrombin III, fibrinogen, and troponin I levels. Data analysis was performed by unpaired T test and Mann-Whitney test. Results: The median antithrombin III level in the acute ischemic stroke group was 93.00%, while in the acute hemorrhagic stroke group was 101.85% (p=0.341). The mean fibrinogen level in the acute ischemic stroke group was 453.46 ± 171.16 mg/dL, while in the acute hemorrhagic stroke group was 399.15 ± 203.02 mg/dL (p=0.302). The median troponin I level in the acute ischemic stroke group was 0.00 ng/mL, while in the acute hemorrhagic stroke group was 0.00 ng/mL (p=0.698). Conclusion: There were no significant differences of antithrombin III, fibrinogen, and troponin I levels between acute ischemic stroke and acute hemorrhagic stroke.